2020
DOI: 10.1017/rdc.2020.118
|View full text |Cite
|
Sign up to set email alerts
|

Erroneously Old Radiocarbon Ages From Terrestrial Pollen Concentrates in Yellowstone Lake, Wyoming, Usa

Abstract: Accelerator mass spectrometry (AMS) dating of pollen concentrates is often used in lake sediment records where large, terrestrial plant remains are unavailable. Ages produced from chemically concentrated pollen as well as manually picked Pinaceae grains in Yellowstone Lake (Wyoming) sediments were consistently 1700–4300 cal years older than ages established by terrestrial plant remains, tephrochronology, and the age of the sediment-water interface. Previous studies have successfully utilized the same laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Radiocarbon dating of pollen concentrates is a method developed for use in lacustrine and freshwater bog sediments (Howarth et al, 2013; Kasai et al, 2021; Neulieb et al, 2013; Newnham et al, 2007; Vandergoes and Prior, 2003), but has yet to be applied to mangrove sediments. Some studies reported pollen reworking from surrounding terrestrial and marine environments, and therefore ages that are too old (Howarth et al, 2013; Kilian et al, 2002; Li et al, 2014; Neulieb et al, 2013; Schiller et al, 2021). Isolating mangrove pollen (an above-ground source that likely formed in situ in the mangrove stand) for radiocarbon dating may reduce the potential of sampling and dating organics that are not representative of the depositional age.…”
Section: Radiocarbon Dating Of Mangrove Sedimentsmentioning
confidence: 99%
“…Radiocarbon dating of pollen concentrates is a method developed for use in lacustrine and freshwater bog sediments (Howarth et al, 2013; Kasai et al, 2021; Neulieb et al, 2013; Newnham et al, 2007; Vandergoes and Prior, 2003), but has yet to be applied to mangrove sediments. Some studies reported pollen reworking from surrounding terrestrial and marine environments, and therefore ages that are too old (Howarth et al, 2013; Kilian et al, 2002; Li et al, 2014; Neulieb et al, 2013; Schiller et al, 2021). Isolating mangrove pollen (an above-ground source that likely formed in situ in the mangrove stand) for radiocarbon dating may reduce the potential of sampling and dating organics that are not representative of the depositional age.…”
Section: Radiocarbon Dating Of Mangrove Sedimentsmentioning
confidence: 99%
“…While some lakes may present relatively simple results (e.g., Tennant et al, 2013 and the FLL results in Figure 6), in other lakes complications may arise that are specific to the dynamics in that particular basin. Basins where regression has exposed old lake sediments (Zimmerman et al, 2018), where deep soils develop and are periodically eroded into the lake (Howarth et al, 2013); and where the potential for unusual carbon dynamics exists (Schiller et al, 2021) demonstrate the need to understand each lake basin as an individual, until enough lakes have been characterized to understand the variety of locations where pollen dating is likely to be successful.…”
Section: Outlook For the Futurementioning
confidence: 99%
“…All but sample OS-144561 were interpreted as erroneously old. The cause of these erroneously old ages is not clear, but old carbon contamination has been documented within the Yellowstone caldera in lake sediments (Schiller et al, 2021) and in organic material entombed in silica sinter (Churchill et al, 2020). It is likely that Goose Lake samples contained old carbon sourced from either reworked sediment, volcanic CO 2 incorporated into plants during photosynthesis (Evans et al, 2010), or volcanic CO 2 in the water column and surficial sediments (Schiller et al, 2021).…”
Section: Chronologymentioning
confidence: 99%